Photocatalytic water splitting over titania supported copper and nickel oxide in photoelectrochemical cell; Optimization of photoconversion efficiency - Mohamed, N.M. (Institute of Physics Publishing, 2018)
We investigated the influence of fluctuating the preparation variables of TiO2 on the efficiency of photocatalytic water splitting in photoelectrochemical (PEC) cell. Hydrothermal associated sol-gel technique was applied to synthesis modified TiO2 with nickel and copper oxide. The variation of water (mL), acid (mL) and total metal loading () were mathematically modelled using central composite design (CCD) from the response surface method (RSM) to explore the single and combined effects of parameters on the system performance. The experimental data were fitted using quadratic polynomial regression model from analysis of variance (ANOVA). The coefficient of determination value of 98 confirms the linear relationship between the experimental and predicted values. The amount of water had maximum effect on the photoconversion efficiency due to a direct effect on the crystalline and the number of defects on the surface of photocatalyst. The optimal parameter ratios with maximum photoconversion efficiency were 16 mL, 3 mL and 5 for water, acid and total metal loading, respectively. Â© Published under licence by IOP Publishing Ltd.